DIALECTIC RELATIONSHIP BETWEEN SOCIO-CULTURAL STATE OF SOCIETY AND ECOLOGICAL CULTURE (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In sciyentific terminology, the sociocultural environment refers to a space that reflects all conditions of human life activity. This environment encompasses all aspects of human life, from daily routines to spiritual and cultural life. The main elements of socioculture include cultural-historical heritage, lifestyle practices, socio-psychological, spiritual-moral, political, and ecological culture. Cultural-historical heritage includes customs, traditions, values, and historical monuments passed down through generations. The artistic environment is associated with cultural treasures such as works of art, architectural monuments, literature, and music. While the socio-psychological environment encompasses sociyetal relationships, customs, and moral norms, spiritual and moral values determine peopleʼs religious beliyefs, ethical values, and spiritual worldviyew. The political environment includes the political system, laws, and governance principles in sociyety, while the ecological environment reflects the relationship betweyen nature and humans.